Use of direct oral anticoagulants is associated with better long-term outcomes in patients with atrial fibrillation and heart failure as compared with vitamin K antagonists. (25th November 2020) - Enzan, N; Matsushima, S; Ide, T; Kaku, H; Tohyama, T; Funakoshi, K; Higo, T; Tsutsui, H
Abstract: Background: Direct oral anticoagulants (DOACs) have been shown to be safe and effective in patients with atrial fibrillation (AF) as compared with warfarin, a vitamin K antagonist. However, the safety and efficacy of DOACs in patients with AF and heart failure (HF) have been unclear. Purpose: The purpose of this study was to determine whether DOACs can improve long-term outcomes in patients with AF and HF as compared with warfarin. Methods: We analyzed the JROADHF registry, which was a multicenter registry of patients hospitalized for the worsening HF in Japan. Baseline data were collected during the episode of index hospitalization from April 2013 to March 2014. Follow-up data were collected up to 4.5 years after the index hospitalization. Patients with AF and creatinine clearance ≥15 ml/min/1.73m 2 were included. Valvular heart disease, congenital heart disease, and constrictive pericarditis were excluded. Eligible patients were divided into two groups according to the use of warfarin or DOACs. The primary outcome was defined as all-cause death. The secondary outcomes were defined as cardiovascular death, composite of all-cause death or cardiovascular hospitalization, and composite of stroke death or stroke related hospitalization. A one to one propensity case-matched analysis was used. Complete case analysis and multiple imputation analysis were also conducted as sensitivity analyses. Results: Out of the 14, 847 patients in this registry, 2, 175 had AF, creatinine clearance ≥15 ml/min/1.73m 2 and discharged alive. Propensity score matching yielded 475 pairs. In matching cohort, mean age was 76.5 years and 513 (54.0%) was male. Mean left ventricular ejection fraction was 48.6±16.4%. During a mean follow-up of 3.2 years, patients with DOACs had a lower incidence rate of all-cause death than those with warfarin (75.2 vs. 99.9 death per 1000 patient-years; rate ratio (RR) 0.75; 95% confidence interval [CI] 0.59–0.96; P=0.022). The incidence of cardiovascular death tended to be lower in DOAC group (30.9 vs. 43.1; incidence rate ratio 0.72; 95% CI 0.49–1.04; P=0.081). There were no significant differences in the incidence of composite of all cause death or cardiovascular hospitalization (252.3 vs. 269.4; RR 0.94; 95% CI 0.79–1.11; P=0.45) or composite of stroke death or stroke related hospitalization (13.1 vs. 16.7; RR 0.79; 95% CI 0.39–1.59; P=0.50). Cox regression model showed that DOAC was associated with lower mortality than warfarin (hazard ratio (HR) 0.75; 95% CI 0.59–0.96; P=0.023). Complete case analysis (HR 0.78; 95% CI 0.63–0.98; P=0.035) and multiple imputation analysis (HR 0.78; 95% CI 0.68–0.84; P<0.001) also showed the same results. A restricted cubic spline analysis demonstrated that the effectiveness of DOACs over warfarin waned with age, and DOACs were effective in patients younger than 80 years old. Conclusion: Use of DOACs was associated with better long-term outcome in patients with HF as compared with warfarin. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Japan Agency for Medical Research and Development